JHS SCIENCE TEACHERS' PERSPECTIVES, PRACTICES, AND CHALLENGES IN TEACHING THE ATOMIC STRUCTURE - Matthew T. Dela Cruz; Almario D. Baltazar Jr., Marie Franz Chua, Mieraflor C. Estrella; Eleonor R. Basilio (CV. ADIBA AISHA AMIRA, 2024)
The concept of atomic structure is a difficult topic to discuss among students and has been one of the teachers’ major concerns for many years. This study was conducted to determine the JHS (Junior High School) science teachers’ perspectives, practices, and challenges in teaching atomic structure in selected public JHS. A survey method was employed, and the quantitative and qualitative results showed that the teacher-respondents had good perspectives, were proficient in the subject matter, and were eager to teach the concept properly. The use of visual aids/models, hand-outs/printed materials, and video lessons/presentations to teach atomic structure is the teachers’ choice and is an invaluable learning material and tool in teaching the atomic structure to JHS students. The main challenges in teaching are the students' low interest and background and the lack of resources and training among teachers on the topic. There is a need for enhanced pedagogical tools, strategies, and skills, as well as training for teachers to support the atomic structure teaching and learning development and progress.